2006
DOI: 10.1021/ef060063o
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Asphaltite−Water Slurries

Abstract: In this study, the rheological characteristics of asphaltite−water slurries (AWSs) were investigated with respect to some of the most important parameters in the preparation of slurries. The effects of pulp density, chemical addition, pulp pH, and particle size on the rheological behavior and viscosity of AWSs were studied. The role of demineralization of asphaltite was also investigated, and rheological properties of raw and relatively demineralized asphaltites were compared. Results showed that viscosity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…pH influences the slurry viscosity by changing the surface charge density of solid particles in the slurry system via hydroxyl anions (OH – ). Researchers have reported that the slurry viscosity values decreased as the pH increased. However, the reduction in viscosity was not significant. Chen et al .…”
Section: Resultsmentioning
confidence: 99%
“…pH influences the slurry viscosity by changing the surface charge density of solid particles in the slurry system via hydroxyl anions (OH – ). Researchers have reported that the slurry viscosity values decreased as the pH increased. However, the reduction in viscosity was not significant. Chen et al .…”
Section: Resultsmentioning
confidence: 99%
“…However, the reduction in viscosity was not significant. 5,34,35 Moreover, the alkali dosage added in the sludge was relatively low (10% of dry sludge, and the solid concentration of the sludge is 13.5%), the sludge mixing ratio in the CSS was also low (Wet sludge: Coal = 15:100), and the solid concentration of CSS was 60%. Given all of this, the alkali proportion in the CSS was approximate 0.12%, and thus the effect of alkali on the slurry viscosity was small and negligible, 36 i.e., the change of slurry viscosity can be deemed as the result of sludge modification.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…Several researchers have investigated the properties of CMC and have published in this and other journals. Those studies have revealed the effectiveness of CMC as an additive, a substrate, a blending material, a stabilizer, a binder, a scaffold material, etc. …”
Section: Introductionmentioning
confidence: 99%